SC Curreent Interruption Capability and Protection of SiC Based Solid State Circuit Breaker. Issue 1 (1st February 2022) - Tian, Mingyu; Ren, Yu; Tian, Shipeng; Tan, Yuchen
Abstract: This paper presents the short circuit (SC) current interruption capability of a 1.7 kV/72 A silicon carbide (SiC) MOSFET based solid state circuit breaker (SSCB). The interruption process of SSCB is introduced in detail. A test platform is built and the SSCB is tested and discussed at various DC-link voltage, fault inductance and junction temperature. Before the desaturation point ( VDS =200 V), SSCB can successfully turn off the SC current. The saturation value of the SC current is positively correlated with di/dt, and the effect of junction temperature (50-150°C) on saturation current is not significant. A SC protection circuit with a response time of 260 ns is proposed and is validated through the test platform.